Pengaruh Penerapan Bundle Ventilator Associated Pneumonia (VAP) Terhadap Insiden Infeksi Pneumonia di Ruang ICU RSUD MM. Dunda Limboto - Pipin Yunus; Susanti Monoarfa; Putri Regina Masi (Universitas Malahayati Lampung, 2025)
ABSTRACT Critical patients with intubation and using ventilators for a long period of time in the ICU are at risk of nosocomial infections called Ventilator Associated Pneumonia (VAP). One of the non-pharmacological therapies carried out is by administering VAP bundles. The purpose of this study was to determine the effect of implementing Ventilator Associated Pneumonia (VAP) Bundles on the Incidence of Pneumonia Infection in the ICU Room of MM Dunda Limboto Hospital. using quantitative pre-experiment involving 15 respondents using purposive sampling. The results of the study using the non-parametric statistical test Wilcoxon signed rank test showed that there was an Effect of the Implementation of Ventilator Associated Pneumonia (VAP) Bundles on the Incident of Pneumonia Infection in the ICU Room of MM Dunda Limboto Hospital as evidenced by the results of p. value (0.001 0.05). The implementation of VAP bundles can be applied as one of the prevention of pneumonia infection incidents in the ICU room Keywords: VAP Bundles, Pneumonia Infection, Ventilator Associated Pneumonia (VAP) ABSTRAK Pasien kritis dengan intubasi dan menggunakan ventilator dalam jangka waktu lama di ICU beresiko terjadi infeksi nosokomial yang disebut Ventilator Associated Pneumonia (VAP). Salah satu terapi non farmakologi yang dilakukan adalah dengan pemberian bundle VAP. Tujuan penelitian ini adalah Untuk Mengetahui Pengaruh Penerapan Bundle Ventilator Associatied Pneumonia (VAP) Terhadap Insiden Infeksi Pneumonia Di Ruang ICU RSUD MM Dunda Limboto. Menggunakan kuantitaif pra eksperimen dengan melibatkan jumlah responden sebanyak 15 orang dengan menggunakan purposivel sampling. Hasil penelitian dengan menggunakan uji statisik non parametrik Wilcoxon signed rank test menunjukkan bahwa terdapat Pengaruh Penerapan Bundle Ventilator Associatied Pneumonia (VAP) Terhadap Insiden Infeksi Pneumonia di Ruang ICU RSUD MM Dunda Limboto dibuktikan dengan hasil p. value (0.001 0.05). Kesimpulan: Penerapan pemberian bundle VAP dapat diterapkan sebagai salah satu pencegahan insiden infeksi pneumonia di ruangan ICU Kata Kunci: Bundle VAP, Infeksi Pneumonia, Ventilator Associatied Pneumonia (VAP).